2018
DOI: 10.1080/13670050.2018.1494131
|View full text |Cite
|
Sign up to set email alerts
|

Using the peabody picture vocabulary test in L2 children and adolescents: effects of L1

Abstract: This study investigated to what extent the Peabody Picture Vocabulary Test (PPVT-4) is a reliable tool for measuring vocabulary knowledge of English as a second language (L2), and to what extent L1 characteristics affect test outcomes. The PPVT-4 was administered to Dutch pupils in six different age groups (4-15 years old) who were or were not following an English educational programme at school. Our first finding was that the PPVT-4 was not a reliable measure for pupils who were correct on maximally 24 items,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 39 publications
7
53
2
Order By: Relevance
“…Based on findings from receptive multilingualism and the study by Goriot et al. (), we hypothesized that cognateness and L1 frequency would explain more variance within the group of lower‐level learners because they might rely more on what they knew from their L1 than would the more advanced learners, who might rely more on their L2 knowledge.…”
Section: The Current Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Based on findings from receptive multilingualism and the study by Goriot et al. (), we hypothesized that cognateness and L1 frequency would explain more variance within the group of lower‐level learners because they might rely more on what they knew from their L1 than would the more advanced learners, who might rely more on their L2 knowledge.…”
Section: The Current Studymentioning
confidence: 99%
“…Goriot et al. () explored the link between word variables related to the first language (L1) and the results on a L2 vocabulary test. The authors tested Dutch learners of English in six different age groups and found that pupils scored higher on test items that were similar to their Dutch translation.…”
Section: Background Literature: Word‐related Variables Involved In Womentioning
confidence: 99%
See 2 more Smart Citations
“…Carrying over of phonological knowledge exemplifies the second type of transfer. Evidence for the transfer of language-specific phonological knowledge has been demonstrated in a recent study on Dutch-speaking children who learn English as a second language (L2) in early foreign language education (Goriot et al, 2018). The children who participated in this study performed better on items of the English version of the Peabody Picture Vocabulary Test (PPVT-III; Dunn & Dunn, 1997), which is a standardized measure of receptive vocabulary, if they are phonologically similar: the closer the English word and its Dutch translation are, the easier the English items are for Dutch-speaking children.…”
Section: Cross-linguistic Influence and The Role Of Language Distancementioning
confidence: 99%